Clustered geographic-opportunistic routing protocol for underwater wireless sensor networks - V. Baranidharan (Journal of Applied Research and Technology, 2020)
The most adverse characteristics of underwater wireless sensor network (UWSN) communications are high propagation delay, high error rate, very low bandwidth, and limited available energy. The energy resources replacement is also more expensive. The proposed clustering-based geographic- opportunistic routing with adjustment of depth-based topology control for communication recovery of void regions (C- GEDAR). The cluster-based GEDAR routes the packet to the surface of sonobuoys with the help of clusters. The void sensor node recovery algorithm is used to recover the void nodes to calculate their new depth. The proposed routing protocol is to be simulated and its performances are evaluated by using an Aquasim simulator. The simulated result shows that C-GEDAR performs better average energy consumption, good packet delivery ratio (PDR) and less end-to-end delay.